The «Group of Twenty», IMF and EU and Reforming of Global Governance - E. J. Il'in (Vestnik MGIMO-Universiteta)
This article is devoted to the process of reforming the global financial system and world economic organizations since the foundation of the International Monetary Fund at the Bretton Woods Conference in 1944 to present time. Special attention is given to results of cooperation of the IMF and the "Group of Twenty"in the context of the world financial crisis 2008-2009. This article mentions the key benchmarks of the historical development of world economy: foundation of the Bretton Woods financial system, rejection of the gold standard at the Jamaica Conference, transition to the floating exchange rates, the wave of crises in the 1990-s, the world financial crisis of 2008-2009. The process of evolution of the IMF within the framework of these global events is considered here. The cooperation of EU, IMF and "Group of Twenty" is considered. The reforms of the IMF and their results are analyzed. The policy of the IMF at different historical stages of its evolution is estimated. As well as it results, the article also deals with the formation and development of the "Group of Twenty". The increasing role of the "Group of Twenty" in the global economic governance and reforming the IMF is considered. Especially is marked the necessity of the further reforms of the IMF and increasing of participation of the "G-20" in the world economic and politic system.